Design and Development of a Web-Based Smart Waste Bank Using the Waterfall Method at the Sari Asri Waste Bank - Muhammad Achidus Syiblih; Muhammad Imron Rosadi (Universitas Mohammad Husni Thamrin, 2026)
However, traditional management of the waste banks is faced by various problems such as the lack of integration of the data recording process, inefficient operation service and the absence of real-time transactions monitoring. The current research paper tries to develop a web-based Smart Waste Bank system using Waterfall model to increase the effectiveness of waste bank management in Bank Sampah Sari Asri. The process of the system development included requirement analysis, system design, implementation, testing and maintenance. The designed system includes multi-role users management, waste collection services via Geographic Information System (GIS), MSME marketplace, approvals and real-time data analytics dashboard. The testing of the developed system was performed using Black Box Testing approach to make sure that all system functions work as expected for the user. The findings show that the developed system successfully integrates all mentioned characteristics and performs all required functions as expected according to testing results. Therefore, the use of the developed system increases the effectiveness of data management, makes operation service more efficient, creates transparency in waste bank management and creates additional economic value due to the integration of the MSME marketplace. Thus, the proposed web-based Smart Waste Bank system can be considered as an efficient and integrated waste bank management solution.